Five Years of Research in Industry, 1926-1930: A Reading List of Selected Articles from the Technical Press - National Research Council (The National Academies Press, 1930)
Keywords: Biography and Autobiography

Memorial Tributes: Volume 21 - National Academy of Engineering (The National Academies Press, 2017)
This is the 21st Volume in the series Memorial Tributes compiled by the National Academy of Engineering as a personal remembrance of the lives and outstanding achievements of its members and foreign associates. These volumes are intended to stand as an enduring record of the many contributions of engineers and engineering to the benefit of humankind. In most cases, the authors of the tributes are contemporaries or colleagues who had personal knowledge of the interests and the engineering accomplishments of the deceased. Through its members and foreign associates, the Academy carries out the responsibilities for which it was established in 1964. Under the charter of the National Academy of Sciences, the National Academy of Engineering was formed as a parallel organization of outstanding engineers. Members are elected on the basis of significant contributions to engineering theory and practice and to the literature of engineering or on the basis of demonstrated unusual accomplishments in the pioneering of new and developing fields of technology. The National Academies share a responsibility to advise the federal government on matters of science and technology. The expertise and credibility that the National Academy of Engineering brings to that task stem directly from the abilities, interests, and achievements of our members and foreign associates, our colleagues and friends, whose special gifts we remember in this book.

The Power of Boldness: Ten Master Builders of American Industry Tell Their Success Stories - Elkan Blout (The National Academies Press, 1996)
"Whatever you dream, begin it, for boldness has genius, power and magic in it." -Goethe What qualities brought America to its dominance of world industry? How will American technology fare in the new global marketplace? What upbringing, education, and personal traits are required to produce leaders who can succeed in this new world? Scan the bookstore shelves and you'll see dozens of attempts by authors to capture the essence of leadership and entrepreneurial success. In The Power of Boldness, the answers come from original sources: ten of the country's most successful business leaders, who share their experiences and insights in individual essays that are remarkable for their directness and personal detail. Six of the writers are inventors who created the enterprises to commercialize their ideas—four assumed management of their fathers' companies and moved into new industrial and geographic markets. Born between 1897 and 1962, these outstanding figures collectively chronicle America's industrial rise since World War II—and share their perspectives on what lies ahead in the age of technology. In engaging and often humorous terms, these men describe how they managed to make the most of the economic and social ups and downs of the past decades—how boldness, clear thinking, and a willingness to learn saw them through the bad times and paved the way to their success. No other book gathers so distinguished a group of business figures: Stephen D. Bechtel, Jr., of Bechtel Group describes the rise, decline, and rise again of the world's largest heavy construction company. William M. Haney, III, of Molten Metal Technology—a strong believer in Goethe's maxim—overviews the opportunities in ecotechnology. Edward C. Johnson 3d, of Fidelity writes on the adventures of a "contrarian" in the financial arena. Gordon E. Moore of Intel explains how his firm became one of the world's largest producers of microprocessor chips and forecasts the future of the electronics industry. John F. Taplin, master inventor and founder of a number of companies, writes on the education of an inventor/entrepreneur. Thomas D. Cabot of Cabot Corporation, Robert Galvin of Motorola, George N. Hatsopoulos of Thermo Electron Corporation, and Ralph Landau of Halcon International, round out this group of master builders of America's industrial power. In an introduction and summing-up, Alfred Chandler, Jr., Pulitzer Prize-winning business historian, explores some of the themes that emerge from the personal essays. Capturing the spirit of innovation as well as the practicalities of business decision making, The Power of Boldness will be required reading for business executives, students of business, and anyone interested in the individual success stories behind America's technological leadership.

Memorial Tributes: Volume 6 - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 1993)
This series presents biographies of deceased members of the National Academy of Engineering.
Keywords: Biography and Autobiography

Memorial Tributes: Volume 4 - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 1991)
Keywords: Biography and Autobiography

Memorial Tributes: Volume 23 - National Academy of Engineering (The National Academies Press, 2021)
This is the twenty-third volume in the series of Memorial Tributes compiled by the National Academy of Engineering as a personal remembrance of the lives and outstanding achievements of its members and foreign associates. These volumes are intended to stand as an enduring record of the many contributions of engineers and engineering to the benefit of humankind. In most cases, the authors of the tributes are contemporaries or colleagues who had personal knowledge of the interests and the engineering accomplishments of the deceased.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 78 - National Academy of Sciences (The National Academies Press, 2000)
Biographic Memoirs: Volume 78 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Memorial Tributes: Volume 24 - National Academy of Engineering (The National Academies Press, 2022)
This is the twenty-fourth volume in the Memorial Tributes series compiled by the National Academy of Engineering as a personal remembrance of the lives and outstanding achievements of its members and international members. These volumes are intended to stand as an enduring record of the many contributions of engineers and engineering to the benefit of humankind. In most cases, the authors of the tributes are contemporaries or colleagues who have personal knowledge of the interests and engineering accomplishments of the deceased.
Keywords: Biography and Autobiography

Memorial Tributes: Volume 22 - National Academy of Engineering (The National Academies Press, 2019)
This is the 22nd Volume in the series Memorial Tributes compiled by the National Academy of Engineering as a personal remembrance of the lives and outstanding achievements of its members and foreign associates. These volumes are intended to stand as an enduring record of the many contributions of engineers and engineering to the benefit of humankind. In most cases, the authors of the tributes are contemporaries or colleagues who had personal knowledge of the interests and the engineering accomplishments of the deceased. Through its members and foreign associates, the Academy carries out the responsibilities for which it was established in 1964. Under the charter of the National Academy of Sciences, the National Academy of Engineering was formed as a parallel organization of outstanding engineers. Members are elected on the basis of significant contributions to engineering theory and practice and to the literature of engineering or on the basis of demonstrated unusual accomplishments in the pioneering of new and developing fields of technology. The National Academies share a responsibility to advise the federal government on matters of science and technology. The expertise and credibility that the National Academy of Engineering brings to that task stem directly from the abilities, interests, and achievements of our members and foreign associates, our colleagues and friends, whose special gifts we remember in this book.
Keywords: Biography and Autobiography

Memorial Tributes: Volume 14 - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2011)
This is the fourteenth volume in the series of Memorial Tributes compiled by the National Academy of Engineering as a personal remembrance of the lives and outstanding achievements of its members and foreign associates. These volumes are intended to stand as an enduring record of the many contributions of engineers and engineering to the benefit of humankind. In most cases, the authors of the tributes are contemporaries or colleagues who had personal knowledge of the interests and the engineering accomplishments of the deceased.
Keywords: Biography and Autobiography

Memorial Tributes: Volume 7 - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 1994)
This series presents biographies of deceased members of the National Academy of Engineering.
Keywords: Biography and Autobiography

Memorial Tributes: Volume 15 - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2011)
This is the fifteenth volume in the series of Memorial Tributes compiled by the National Academy of Engineering as a personal remembrance of the lives and outstanding achievements of its members and foreign associates. These volumes are intended to stand as an enduring record of the many contributions of engineers and engineering to the benefit of humankind. In most cases, the authors of the tributes are contemporaries or colleagues who had personal knowledge of the interests and the engineering accomplishments of the deceased.
Keywords: Biography and Autobiography

Memorial Tributes: Volume 17 - National Academy of Engineering (The National Academies Press, 2013)
This is the 17th Volume in the series Memorial Tributes compiled by the National Academy of Engineering as a personal remembrance of the lives and outstanding achievements of its members and foreign associates. These volumes are intended to stand as an enduring record of the many contributions of engineers and engineering to the benefit of humankind. In most cases, the authors of the tributes are contemporaries or colleagues who had personal knowledge of the interests and the engineering accomplishments of the deceased. Through its members and foreign associates, the Academy carries out the responsibilities for which it was established in 1964. Under the charter of the National Academy of Sciences, the National Academy of Engineering was formed as a parallel organization of outstanding engineers. Members are elected on the basis of significant contributions to engineering theory and practice and to the literature of engineering or on the basis of demonstrated unusual accomplishments in the pioneering of new and developing fields of technology. The National Academies share a responsibility to advise the federal government on matters of science and technology. The expertise and credibility that the National Academy of Engineering brings to that task stem directly from the abilities, interests, and achievements of our members and foreign associates, our colleagues and friends, whose special gifts we remember in this book.
Keywords: Biography and Autobiography

Memorial Tributes: Volume 5 - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 1992)
Keywords: Biography and Autobiography

Memorial Tributes: Volume 20 - National Academy of Engineering (The National Academies Press, 2016)
This is the 20th Volume in the series Memorial Tributes compiled by the National Academy of Engineering as a personal remembrance of the lives and outstanding achievements of its members and foreign associates. These volumes are intended to stand as an enduring record of the many contributions of engineers and engineering to the benefit of humankind. In most cases, the authors of the tributes are contemporaries or colleagues who had personal knowledge of the interests and the engineering accomplishments of the deceased. Through its members and foreign associates, the Academy carries out the responsibilities for which it was established in 1964. Under the charter of the National Academy of Sciences, the National Academy of Engineering was formed as a parallel organization of outstanding engineers. Members are elected on the basis of significant contributions to engineering theory and practice and to the literature of engineering or on the basis of demonstrated unusual accomplishments in the pioneering of new and developing fields of technology. The National Academies share a responsibility to advise the federal government on matters of science and technology. The expertise and credibility that the National Academy of Engineering brings to that task stem directly from the abilities, interests, and achievements of our members and foreign associates, our colleagues and friends, whose special gifts we remember in this book.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 76 - National Academy of Sciences (The National Academies Press, 1999)
Biographic Memoirs: Volume 76 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Memorial Tributes: Volume 18 - National Academy of Engineering (The National Academies Press, 2014)
This is the 18th Volume in the series Memorial Tributes compiled by the National Academy of Engineering as a personal remembrance of the lives and outstanding achievements of its members and foreign associates. These volumes are intended to stand as an enduring record of the many contributions of engineers and engineering to the benefit of humankind. In most cases, the authors of the tributes are contemporaries or colleagues who had personal knowledge of the interests and the engineering accomplishments of the deceased. Through its members and foreign associates, the Academy carries out the responsibilities for which it was established in 1964. Under the charter of the National Academy of Sciences, the National Academy of Engineering was formed as a parallel organization of outstanding engineers. Members are elected on the basis of significant contributions to engineering theory and practice and to the literature of engineering or on the basis of demonstrated unusual accomplishments in the pioneering of new and developing fields of technology. The National Academies share a responsibility to advise the federal government on matters of science and technology. The expertise and credibility that the National Academy of Engineering brings to that task stem directly from the abilities, interests, and achievements of our members and foreign associates, our colleagues and friends, whose special gifts we remember in this book.
Keywords: Biography and Autobiography

Memorial Tributes: Volume 13 - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2010)
This is the thirteenth volume in the series of Memorial Tributes compiled by the National Academy of Engineering as a personal remembrance of the lives and outstanding achievements of its members and foreign associates. These volumes are intended to stand as an enduring record of the many contributions of engineers and engineering to the benefit of humankind. In most cases, the authors of the tributes are contemporaries or colleagues who had personal knowledge of the interests and the engineering accomplishments of the deceased.
Keywords: Biography and Autobiography

Memorial Tributes: Volume 16 - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2012)
This is the 16th Volume in the series Memorial Tributes compiled by the National Academy of Engineering as a personal remembrance of the lives and outstanding achievements of its members and foreign associates. These volumes are intended to stand as an enduring record of the many contributions of engineers and engineering to the benefit of humankind. In most cases, the authors of the tributes are contemporaries or colleagues who had personal knowledge of the interests and the engineering accomplishments of the deceased. Through its members and foreign associates, the Academy carries out the responsibilities for which it was established in 1964. Under the charter of the National Academy of Sciences, the National Academy of Engineering was formed as a parallel organization of outstanding engineers. Members are elected on the basis of significant contributions to engineering theory and practice and to the literature of engineering or on the basis of demonstrated unusual accomplishments in the pioneering of new and developing fields of technology. The National Academies share a responsibility to advise the federal government on matters of science and technology. The expertise and credibility that the National Academy of Engineering brings to that task stem directly from the abilities, interests, and achievements of our members and foreign associates, our colleagues and friends, whose special gifts we remember in this book.
Keywords: Biography and Autobiography

Memorial Tributes: Volume 12 - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2008)
This series contains short biographies of deceased members of the National Academy of Engineering.
Keywords: Biography and Autobiography